Acceptance on Mobile Learning via SMS: A Rasch Model Analysis - Ismail, Issham; Mohammed Idrus, Rozhan; Mohd Johari, Siti Sarah (International Journal of Interactive Mobile Technologies (iJIM), 2010)
This study investigated whether mobile learning via Short Message Service (SMS-learning) is accepted by the students enrolled in the distance learning academic programme in the Universiti Sains Malaysia. This study explored the impact of perceived usefulness, perceived ease of use and usability of the system to their acceptability. The survey was constructed using a questionnaire consisting of statements regarding the participantsâ?? demographics, experiences in and perception of using mobile learning via SMS, involving 105 students from management and sciences disciplines. The Rasch Model Analysis was used for measurement correspond to a 5 point Likert. Results indicated that the usability of the system contributed to be effectiveness in assisting the students with their study. Respondents agree that SMS-learning is easy, effective and useful to help them study. However, the results found that there has been a problem in mobile learning that less interaction with lecturers. It implies that the acceptability of students to this mode on communication and interaction is highly endorsed.